Incidence, risk factors and mortality of nosocomial pneumonia in Intensive Care Units: A prospective study - Voss Andreas; Aygen Bilgehan; Yıldız Orhan; Güven Muhammet; Alp Emine; Doganay Mehmet (BMC, 2004)
Abstract To determine the frequency, risk factors and mortality of nosocomial pneumonia a prospective study was conducted in the intensive care units. In the study period, 2402 patients were included. The nosocomial pneumonia was defined according to the Centers for Disease Control Criteria. Overall, 163 (6.8%) of the patients developed nosocomial pneumonia and 75.5% (n = 123) of all patients with nosocomial pneumonia were ventilator-associated pneumonia. 163 patients who were admitted to the intensive care unit during the same period but had no bacteriologic or histologic evidence of pneumonia were used as a control group. The APACHE II score, coma, hypoalbuminemia, mechanical ventilation, tracheotomy, presence of nasogastric tube were found as independent risk factors. Crude and attributable mortality were 65% and 52.6%, respectively. The mortality rate was five times greater in the cases (OR: 5.2; CI 95%: 3.2-8.3). The mean length of stay in the intensive care unit and hospital in the cases were longer than controls (p < 0.0001). Patients requiring mechanical ventilation have a high frequency of nosocomial pneumonia.